Kontribusi Ekonomi Perempuan, Tekanan Ekonomi dan Kesejahteraan Keluarga pada Keluarga Nelayan dan Buruh Tani Bawang Merah - Puspitawati, Herien; Putri, Artika Chandra Julian; Titipani, Anadia; Khasanah, Muwakhidah Nur (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
Most farmers and fishermen in Indonesia have limitations in meeting economic, social, and other standard needs. This limitation shows the low level of family well-being. This study aims to analyze the characteristics of fishermen and onion farm laborers, women's economic contributions, economic pressures and family well-being. The location of the study was carried out at two locations, in Kali Adem Muara Angke and Losari Lor Village, with a participants of 130 respondents (60 fisherman's wives and 70 wives onion farm workers). The data collected in this study are primary data (interview method). Data processing and analysis are carried out descriptively and inferently (t-test and regression). The results showed that the economic contribution made by the fishermen's family was greater than that of the onion farmer family. The families of fishermen and onion farm workers in this study both in the sea / harvest season and in the season do not go to sea / famine included in the category of moderate economic pressure. Family well-being experienced by the families of fishermen and workers' families both in the sea / harvest season and in the season does not go to sea / famine including the medium category. The effect test shows that the variable number of family members and income per capita have a significant positive influence on family well-being. In addition, economic pressure variable has a significant negative influence on family well-being.